Implications for sequencing of biologic therapy and choice of second anti‐TNF in patients with inflammatory bowel disease: results from the IMmunogenicity to Second Anti‐TNF therapy (IMSAT) therapeutic drug monitoring study. Issue 8 (29th August 2022) - Chanchlani, Neil; Lin, Simeng; Auth, Marcus K.; Lee, Chai Leng; Robbins, Helena; Looi, Shi; Murugesan, Senthil V.; Riley, Tom; Preston, Cathryn; Stephenson, Sophie; Cardozo, Wendy; Sonwalkar, Sunil A.; et al.
Summary: Background: Anti‐drug antibodies are associated with treatment failure to anti‐TNF agents in patients with inflammatory bowel disease (IBD). Aim: To assess whether immunogenicity to a patient's first anti‐TNF agent would be associated with immunogenicity to the second, irrespective of drug sequence Methods: We conducted a UK‐wide, multicentre, retrospective cohort study to report rates of immunogenicity and treatment failure of second anti‐TNF therapies in 1058 patients with IBD who underwent therapeutic drug monitoring for both infliximab and adalimumab. The primary outcome was immunogenicity to the second anti‐TNF agent, defined at any timepoint as an anti‐TNF antibody concentration ≥9 AU/ml for infliximab and ≥6 AU/ml for adalimumab. Results: In patients treated with infliximab and then adalimumab, those who developed antibodies to infliximab were more likely to develop antibodies to adalimumab, than patients who did not develop antibodies to infliximab (OR 1.99, 95%CI 1.27–3.20, p  = 0.002). Similarly, in patients treated with adalimumab and then infliximab, immunogenicity to adalimumab was associated with subsequent immunogenicity to infliximab (OR 2.63, 95%CI 1.46–4.80, p  < 0.001). For each 10‐fold increase in anti‐infliximab and anti‐adalimumab antibody concentration, the odds of subsequently developing antibodies to adalimumab and infliximab increased by 1.73 (95% CI 1.38–2.17, p  < 0.001) and 1.99 (95%CI 1.34–2.99, p  < 0.001), respectively. Patients who developed immunogenicity with undetectable drug levels to infliximab were more likely to develop immunogenicity with undetectable drug levels to adalimumab (OR 2.37, 95% CI 1.39–4.19, p  < 0.001). Commencing an immunomodulator at the time of switching to the second anti‐TNF was associated with improved drug persistence in patients with immunogenic, but not pharmacodynamic failure. Conclusion: Irrespective of drug sequence, immunogenicity to the first anti‐TNF agent was associated with immunogenicity to the second, which was mitigated by the introduction of an immunomodulator in patients with immunogenic, but not pharmacodynamic treatment failure. Abstract : In 1058 patients with inflammatory bowel disease who underwent therapeutic drug monitoring for both infliximab and adalimumab, those who developed antibodies to a first anti‐TNF were more likely to develop antibodies to a second anti‐TNF, irrespective of drug sequence. Commencing an immunomodulator at the time of switching to the second anti‐TNF was associated with improved drug persistence in patients with immunogenic but not pharmacodynamic failure.